Tiberal (Ro 7-0207-Roche) in the Treatment of Intestinal Amoebiasis - Part II - Sunoto Sunoto; S. H. Pudjiadi; Suharjono Suharjono; Z. Sulaiman (Paediatrica Indonesiana, 1976)
Twenty-four intestinal amoebiasis patients have been treated with a new amoebicid tiberal (Roche) or metronidazole as a control in a dosage of 15- 30 mg/kg body weight per day for 5 consecutive days. The results show that both drugs achieve a 100% cure rate. No side effects or signs of drug toxicity as evaluated from the results of the safety tests were observed. No signs of clinical or parasitological relapses were seen (after discharge. In comparison with the previous trial with a lower dosage (7~ - 15 mg.) and longer course (7 days) the results were even better, e.g. clinical improvement and parasitological disappearance were achieved in a shorter time.